Stylistics and narrative discourse analysis The story (The Story of the Professor Who...!!) by Ahmed Nasr is an example (Sebha University Conference Proceedings, 2024)
The stylistic study of the literary text seeks to highlight its language as a first and foremost source; given the roots of the emergence of stylistics and its close relationship to language and general linguistics, i.e. linguistics, and given that it is a formal approach in the study of the language of the literary text, it must be the study of language and probing it The main entrance to the study of stylistic features in literary works The stylistic should take care of all levels of the text, to complete the procedures for revealing the characteristics of the text from sound, morphology, composition, significance and indication of their effects. In the literary text, the study aims to approach the narrative text (the story of the professor who..!!) stylistic approach, and to identify the stylistic manifestations and know the characteristics of the style of the writer of the text and how he dealt with language in the formulation of his text. The questions in this research are those used by the researcher as a goal to know and understand the beauty or art of the sentence used, including how the writer was able to build the characters of his text through language in the story "The story of the professor who..!!" by Ahmed Nasr? What is the relationship betwee pronunciation or sentence and style in the story